Carbon Capture and Resource Utilization by Algal–Bacterial Consortium in Wastewater Treatment: A Mini-Review - Yu, Ting; Wang, Siya; Yang, Hui; Sun, Yuxin; Chen, Zhongtai; Xu, Guangjing; Zhang, Cuiya (Water (Basel), 2024)
This review critically evaluates the algal–bacterial consortium (ABC) as a promising technology for wastewater treatment, carbon capture and storage, while also assessing its challenges and opportunities. The ABC system, characterized by the coupling of algae and bacteria, not only removes pollutants and reclaims resources but also helps in reducing greenhouse gas emissions. This system harnesses algal photosynthesis and bacterial degradation of organic matters to establish a carbon cycle, enhancing biomass production and pollutant removal. Despite its promise, the ABC process is subject to several hurdles, including sensitivity to low temperatures, reliance on artificial illumination, and the potential for algal biomass contamination by toxic substances. To capitalize on its full potential, continued research and technological advancements are imperative. Future investigations should focus on optimizing the system’s operational efficiency, developing precise process models, exploring avenues for resource recovery, and broadening the scope of its applications. By surmounting these challenges, the ABC system has the capacity to make a significant impact on sustainable wastewater management and carbon fixation.